'Here and There': Children and Youth's Perspectives of Borders in Mexico–United States Migration. (11th June 2019) - Oliveira, Gabrielle
Abstract : This article explores children's perspectives regarding migration and family separation on both sides of the Mexico‐U.S. border. 'Transnational care constellations' 1 that connect separated siblings allow children to imagine the other side of the border and to explore their thoughts and perspectives through the lenses of inequality, as well as through a sense of belonging and family. This article presents ethnographic data of families that capture the dynamism of families that are both 'here and there' as children assemble their ideas and narratives of how transnational lives exist.